PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. BANK RAKYAT INDONESIA (PERSERO), Tbk. KANTOR WILAYAH PEKANBARU - Ogi Rifansyah; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this study was to determine the effect of transformational leadership style and organizational culture on employee performance PT. Bank Rakyat Indonesia (Persero), Tbk. Regional Office Pekanbaru. This research was conducted at PT. Bank Rakyat Indonesia (Persero), Tbk. Pekanbaru Regional Office located in the Sudirman Block E Plot No.1, RT.01 / RW.01, Simpang Tiga village, subdistrict Bukit Raya.In this research method used is the method of statistical tests with SPSS, where samples were used that employees of PT. Bank Rakyat Indonesia (Persero), Tbk. Pekanbaru Regional Office and as an informant to interview is with the HRD of PT. Bank Rakyat Indonesia (Persero), Tbk. Regional Office Pekanbaru. To determine the sample using census techniques and data collection techniques with interviews and questionnaires.From the results of data analysis include validity, reliability test, t-test, f, and multiple linear regression showed that transformational leadership style and organizational culture has an influence on the performance of employees at PT. Bank Rakyat Indonesia (Persero), Tbk. Pekanbaru Regional Office with a value of 0.777 means that the influence of variable transformational leadership style and organizational culture on employee performance variables was 77.7%. Hypothesis testing results showed that the f-count is greater than f-table which means Ha accepted.Keywords: Transformational Leadership Style, Organizational Culture and Employee Performance